Os recortes e as bordas - Cunha, Olívia Maria Gomes da (Afro-Ásia, 2023)
Resenha de: PRICE, Richard. Inside/Outside: Adventures in Caribbean History and Anthropology. Athens: University of Georgia Press, 2022. 272 p.